Overexpression of IL-10 in C2D macrophages promotes a macrophage phenotypic switch in adipose tissue environments - Xie, Linglin; Fu, Qiang; Ortega, Teresa M.; Zhou, Lun; Rasmussen, Dane; O’Keefe, Jacy; Zhang, Ke K.; Chapes, Stephen K. (My University, 2014)
Adipose tissue macrophages are a heterogeneous collection of classically activated (M1) and alternatively activated (M2) macrophages. Interleukin 10 (IL-10) is an anti-inflammatory cytokine, secreted by a variety of cell types including M2 macrophages. We generated a macrophage cell line stably overexpressing IL-10 (C2D-IL10) and analyzed the C2D-IL10 cells for several macrophage markers after exposure to adipocytes compared to C2D cells transfected with an empty vector (C2D-vector). C2D-IL10 macrophage cells expressed more CD206 when co-cultured with adipocytes than C2D-vector cells; while the co-cultured cell mixture also expressed higher levels of Il4, Il10, Il1β and Tnf. Since regular C2D cells traffic to adipose tissue after adoptive transfer, we explored the impact of constitutive IL-10 expression on C2D-IL10 macrophages in adipose tissue in vivo. Adipose tissue-isolated C2D-IL10 cells increased the percentage of CD206+, CD301+, CD11c−CD206+ (M2) and CD11c+CD206+ (M1b) on their cell surface, compared to isolated C2D-vector cells. These data suggest that the expression of IL-10 remains stable, alters the C2D-IL10 macrophage cell surface phenotype and may play a role in regulating macrophage interactions with the adipose tissue.
Keywords: Macrophages; Adipose tissue; Interleukin 10